Research on the Classification of Body Type and Prototype of Middle-aged Women based on 3D Scanning (Journal of Fiber Bioengineering and Informatics, 2020)
The human body shape is the foundation of clothing structure design, it is important to analyze bodyshape accurately to satisfy people's demand for the fitness of clothing. With the improvement of people'srequirements for the fit of clothing, the classification of body type is gradually refined. As a large groupconsumers of clothing products, middle-aged female body shapes are different from young and olderwomen. This paper was based on the 3D human body measurement technology. 211 females' body dataaged from 50 to 59 in central China were used as experiment samples. There are 26 body part sizes intotal, including length, width and girth. Through the data analysis software SPSS, five types of bodyshape are obtained based on cluster analysis. Then the models of various types of middle-aged womenwere reconstructed, the specific characteristics of various types of body types were explained. Finally, theinfluence of body shape difference on the prototype version was studied by comparing the correspondingupper prototype of each body type. The research results of this paper can provide reference for thedevelopment of middle-aged women’s upper prototype.